Medical faculty and students’ perceived incivility in virtual classes during the COVID-19 lockdown: A qualitative study - Nematullah Shomoossi; Marzie Torkmannejad Sabzevari; Mostafa Rad (Research and Development in Medical Education)
Background: After the COVID-19 lockdown and the dominance of virtual classes in medical education, variant dimensions of incivility emerged and required further exploration. The present study was designed to explore and describe incivility in virtual classes as perceived by students and faculty members. Methods: This qualitative study involved 55 students and 38 faculty members who were recruited by purposive sampling at a major medical university in Iran. Open-ended questions and semi-structured in-depth interviews were used to elicit the participants’ perceptions of incivility in virtual classes. The narrative responses were analyzed by conventional content analysis. Results: Nine major categories were extracted, four of which contained students’ incivility (Irresponsibility, dishonesty, unreasonable expectations, and disruptive behavior in virtual classes); and five categories reflected faculty incivility (Lack of accountability, inappropriate classroom management, unfair academic evaluation, disruptive behavior in virtual classes, and inappropriate interactions with students). Conclusion: The students’ and faculty incivility as explored in the present study suggests acknowledging them by stakeholders (students, faculty, and educational management) to expedite effective management of virtual learning and teaching at universities.